NILAI EDUKASI DAN BUDAYA DALAM SYAIR-SYAIR KERAJAAN BIMA - Mayong Mayong; Akmal Hamsa; Muhammad Alfian Tuflih (20-87-2496)
Abstract: Educational and Cultural Values in the Poems of the Kingdom ofBima. This study aims to: 1) examine the educational value contained in thepoems of the Bima Kingdom; and 2) examine the cultural values contained in thepoems of the Bima Kingdom. This research is a qualitative research using aqualitative descriptive research design. The subject of this research is the poetryof the Kingdom of Bima, while the object of research is the educational andcultural values contained in these poems. The data analysis model used in thisstudy adopts an interactive data analysis model which consists of four activitystreams namely data collection, data reduction, data presentation, and drawingconclusions. The results of this study indicate that there are various educationaland cultural values in the poems of the Bima Kingdom.